Measuring Quality in Libraries - Bayır, Didar; Simpson, Bill (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
This paper is based on the proceedings of a Seminar held at the Bibliothèque Nationale in Paris on 23 March 2007. The Seminar involved 26 invited participants from eleven countries and included nine presentations followed by detailed discussion and the exchange of ideas. The broad themes were: Tools for Quality Measurement, Standards and Performance Indicators, Benchmarking and Auditing. The Seminar’s agreed purpose was to identify the available tools, such as LibQUAL+ and ISO standards, to explore the results of the assessments undertaken, to identify actions to take forward, to look at the issues involved from a European perspective and to identify the basis for comparisons across Europe.